The Application of Domino Card Media in The Subject of The Qur'an Hadith Surah At-Tin Material Class V at MIMA 01 KH. Shiddiq Jember - Syah B, Alwi Ristaman; Nor Hakim, Muh. (Rausyan Fikri Journal of Islamic Studies, 2024)
This study is based on several problems found in class V.C students at MIMA 01 KH. Shiddiq Jember. The problem is related to the motivation of students in following the Al-Qur'an Hadith lessons which are less enthusiastic. As students admit that the Al-Qur'an Hadith is one of the subjects that is considered difficult. Therefore, it is necessary to use interesting learning media that can increase the enthusiasm of students in following the Al-Qur'an Hadith lessons. The media offered is a domino card on the subject of the letter at-Tin. This study aims to determine the results of the application of domino card learning media. Domino card learning media is a media to support quality learning, by using this domino card learning media as an alternative when learning is considered less interesting or monotonous. This study uses a descriptive qualitative research method. The data collection techniques used are interviews, observations and documentation. This study found that domino card media can be a new breakthrough for educators to realize interesting and quality learning. The strategies that can be carried out by educators are three stages of activities, namely planning, implementation, and evaluation of the use of domino card media in the Al-Qur'an Hadith subject on the material of the letter at-Tin.